Optimalisasi Pembelajaran Koperasi dengan Kekuatan Digital Storytelling - Ariyanti Ariyanti (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2021)
Economic learning cooperative material in class X SMA often leads to confusion and foreign effects on students, because there is no